Fluorogenic selective and differential medium for isolation of fecal streptococci. - Littel, K J (1983)
Of 44 fluorogenic substrates tested for their ability to differentiate species of fecal streptococci, four yielded species-differentiating reactions. The remaining substrates either yielded uniformly positive, negative, or variable strain-dependent reactions. One substrate, 4-methylumbelliferone-alpha-D-galactoside, was hydrolyzed by Streptococcus bovis and S. faecium and its biotypes. 4-Methylumbelliferone-alpha-D-galactoside and a colorimetric starch substrate were incorporated into the fecal streptococcal selective medium of Donnelly and Hartman (Appl. Environ. Microbiol. 35:576-581, 1978). Three phenotypic groups were identifiable on the new fluorescent gentamicin-thallous-carbonate agar: (i) starch hydrolysis and fluorescence (S. bovis), (ii) no starch hydrolysis but fluorescence (S. faecium and its biotypes), and (iii) no starch hydrolysis or fluorescence (S. faecalis, S. avium, S. equinus, S. mitis, and S. salivarius). Of the presumptive identifications from sewage, swine, and bovine samples, 86% were confirmed as being correct. The new medium has potential application in water, food, environmental, and possibly clinical microbiology.